Deutsche Söldner im Italien des Trecento - Selzer, Stephan 1968- (Bibliothek des Deutschen Historischen Instituts in Rom, 2001)
The 14th century was the high-point of German mercenary activity in the service of Italian princes and cities. For the first time in 60 years, this study addresses the multifarious implications of this intriguing subject. On the basis of newly discovered sources, it analyzes the general parameters defining international mercenary service in 14th century Italy and describes the life-situations of German mercenaries in war and peacetime. Inquiry into the motives of the mercenaries extends the purview to their geographical origins north of the Alps.